STUDIES OF POTASH BEARING EVAPORITE BASINS OF KOHAT KARAK SALT RANGE, NWFP PAKISTAN (Biological Sciences - PJSIR, 2022)
Potash-bearing minerals occur in nature with common salt and usually deposited in the evaporite basin on evaporationof brine water. In view of the huge deposits of common salt in Pakistan, particularly in Kohat-Karak evaporitebasin, NWFP; investigations to locate the potash deposits in the common salt of the area were undertaken. The geologyof the potash bearing deposits reveal their occurance in the form of lenticular beds associated with rock salts. Thepresent study has successfully brought into focus areas of potash concentration in the above area which after refiningmay be exploited to meet the requirement of potash for fertilizer.